Pomiędzy rekonstrukcją, odtwórstwem a inscenizacją, czyli próba analizy zjawiska rekonstrukcji historycznej - Stulgis, Magdalena Maria (Pamięć i Sprawiedliwość, 2013)
The author undertakes the attempt to analyse an increasingly popular in Poland phenomenon of historical reconstruction. She refers to such terminological issues as historical reconstruction, historical recreation, staging, mistakenly regarded as homogenous. In order to distinguish between the above mentioned definitions, she additionally specifies the reconstruction levels as represented in a particular environment. The article contains a review of main problems connected with reconstruction and its perception, issues of ethics and morality included. Moreover, she presents an outline of the history of the reconstruction movement both in the world and in Poland. The author tries to reveal, step by step, the mechanism of the formation of historical reconstruction groups and similar associations, beginning with a gathering of the people interested in forming the group through the selection of its name and the vision of its activities, up to collecting the equipment. This process results in the emergence and development of a separate reconstruction environment where those who share the common passion have a chance to exchange experience and knowledge. The text also describes the forms of activities practised by the performers (apart from specific recreations) and their tasks. It is connected with the presentation of objectives, the historical reconstruction tries to achieve and which stand behind the reconstruction performers’ motivations. The article shows merits of the phenomenon, not ignoring, at the same time, its deficiencies and potential threats. The author also tries to answer the question: what the historical education provided by historical reconstruction should be based upon?